Local Democracy in the Kingdom of Balanipa and the Genealogy of Civic Culture - Randiawan, Randiawan; Supratman , Andi; Khaedir , Muh. (Universitas Muhammadiyah Makassar, 2026)
Studies on local democracy in Indonesia are still dominated by modern institutional perspectives that tend to ignore local wisdom-based political practices, including the experiences of traditional kingdoms in the archipelago. The Balanipa Kingdom in Mandar is one of the local political entities that demonstrates practices of power based on deliberation, customary legitimacy, and collective participation, but it has not been widely studied in the context of political culture and the formation of civic culture. This study aims to analyze the transformation of the political culture of the Balanipa Kingdom from a traditional power structure to the formation of a civic culture among the Mandar people. The research uses a historical-interpretative approach and library research combined with a socio-political genealogy perspective using historical documents and academic studies on political culture and local democracy. The analysis is conducted through historical interpretation and conceptual synthesis to identify the relationship between customary values, government structures, and the civic orientation of the community. The results of the study show that the Balanipa system of government is not an absolute monarchy, but contains deliberative mechanisms through customary institutions such as Appeq Banua Kayyang, which functions as a check on Mara'dia's power. The values of deliberation (sirumung karaya), consensus (assamaturuang), and solidarity (sikalulu) form the participatory and collective political orientation of the community, transforming into a civic culture that shapes social participation and political legitimacy. This study concludes that local democracy has developed historically in the Mandar tradition through customary institutions. The novelty of this research lies in the integration of local political history analysis with political culture and civic culture theory. This study contributes an alternative perspective that Indonesian democracy can be strengthened through the revitalization of local political values as the foundation of substantive democracy based on cultural wisdom